Development of Active CO2 Emission Control for Diesel Engine Exhaust Using Amine-Based Adsorption and Absorption Technique - Solomon Jenoris Muthiya; L. Natrayan; L. Yuvaraj; Mohankumar Subramaniam; Joshuva Arockia Dhanraj; Wubishet Degife Mammo (Adsorption Science & Technology)
Diesel-powered transportation is considered an efficient method of transportation; this sees the increase in the demand for the diesel engine. But diesel engines are considered to be one of the largest contributors to environmental pollution. The automobile sector accounts for the second-largest source for increasing CO2 emission globally. In this experiment, a suitable postcombustion treatment to control CO2 emission from IC engine exhaust is developed and tested. This work focuses to control CO2 emission by using the chemical adsorbent technique in diesel engine exhaust. An amine-based liquid is used to adsorb the CO2 molecules first and absorb over the amines from the diesel engine exhaust. Three types of amino solutions (L-alanine, L-aspartic acid, and L-arginine) were prepared for 0.3 mole concentrations, and the CO2 absorption investigation is performed in each solution by passing the diesel exhaust. A suitable CO2 adsorption trap is developed and tested for CO2 absorption. The experiments were performed in a single-cylinder diesel engine under variable load conditions. The eddy current dynamometer is used to apply appropriate loads on the engine based on the settings. The AVL DIGAS analyzer was used to measure the CO2, HC, and CO emissions. An uncertainty analysis is carried out on the experimental results to minimize the errors in the results. The effective CO2 reduction was achieved up to 85%, and simultaneous reduction of HC and CO was also observed.